Multi-Temporal Identification and Analysis of Land Surface Deformation with Land Use Land Cover in Makassar City - Suharman Hamzah; Regita Faridatunisa Wijayanti; Ira Mutiara Anjasmara; Laode M Sabri; Anas Osman (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2026)
Rapid urbanization heightens the risk of land subsidence in Makassar City. Aim: This study analyzes and maps land surface deformation alongside Land Use and Land Cover (LULC) dynamics from 2020–2024. Methodology and Results by integrating multitemporal Sentinel-1 SAR (VV polarization) and supervised LULC classification from Landsat-8 on the Google Earth Engine platform. Annual LULC maps were produced using an SVM, yielding high accuracy (Kappa 0.893–0.988). Built-up land expanded mainly at the expense of vegetation and bare land. Deformation was inferred from temporal differences in VV backscatter (VV_diff); statistics were computed for each class. Negative VV_diff values were frequently observed in built-up and bareland areas, indicating subsidence. Significant interannual variability was observed in 2023-2024, particularly within the vegetation zones. Linear regression confirmed a strong negative deformation trend in built-up areas (slope −0.0123 dB/year). These results demonstrate a linkage between urban expansion and ground deformation. Conclusion, significance, and impact study: The approach provides a repeatable and cost-effective framework for continuous subsidence monitoring using open satellite data. GEE facilitates the open replication of workflows. The findings contribute to the field of urban planning and policy by identifying vulnerable zones, promoting risk-aware land allocation, infrastructure maintenance, and sustainable development methods for Indonesian coastal megacities and other rapidly expanding metropolitan areas.